Psikobiotik: Peran Mikrobiota Usus Dalam Kesehatan Jiwa - Fachry Naufal; Diaru Fauzan Farizy; Winda TU (Medula, 2020)
Inside human body, beneficial microbes reside on or within tissues. Recent studies show that the gut microbiota plays an important role in mental health – they are linked to the brain by the gut-brain axis. The gut-brain axis is a complex neurohumoral communication network and take a role from maintaining the central nervous system function to metabolic homeostasis. Psychobiotic is defined as a living organism which benefits mentally ill patients. Psychobiotics increases neurotransmitter production in the gut, including dopamine (DA), serotonin (5-HT), noradrenaline (NA), and γ-aminobutyric acid (GABA), which modulates neurotransmitters transmission on proximal synapse in enteric nervous system. Researchers conduct studies which makes several strains of psychobiotics consumed as probiotics, as a form of intervention to several types of psychiatric patients, such as patients with anxiety, depression, schizophrenia, autism, Parkinson disease, Alzheimer, to multiple sclerosis. After the duration of the intervention, assessments are done by questionnaires and samples are taken from the patient’s stool. Researchers found that psychobiotics gives therapeutic effects and a positive outcome to mentally ill patients that are seen from elevated mood, improved depression, and improved overall mental health, so it has a potential as an intervention to several mental disorders, aside from pharmacological therapy.